Agrobacterium- mediated transformation of Turkish upland rice (Oryza sativa L.) for Dalapon herbicide tolerance - (:unkn) unknown (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2020)
Agrobacterium-mediated transformation of upland rice is established in few numbers of cultivars due to the high cultivar-specificity of regeneration from transformed explants. Further, dehalogenase E (dehE) gene had been characterized in Pseudomonas putida and it produces an enzyme that degrades dalapon. This study aimed to transform Turkish upland rice with the dehE herbicide resistant gene and addresses the challenges of transgenic rice recovery by identifying explant and transformation method. Constructed vector pCAMdehE carrying dehE gene was transferred into the rice shoot apex by Agrobacterium-mediated transformation. The transformed rice was analyzed for expression of the transgenes by polymerase chain reaction (PCR). Herbicide resistance leaf painting assay was carried out at different dalapon herbicide concentrations to the transgenic rice leaves. Transformation efficiency percentage (putative) was highest (32.66%) in 5 days old explants. PCR analysis resulted in the amplification of the dehE, T-DNA border endonuclease (virD2) and hygromycin phosphotransferase (hpt) genes from the transgenic rice. In addition, dehalogenase activity was proved with higher dalapon tolerance in the rice. Dalapon effects started to appear in the transformed rice at 180 mg/l, while in non-transformed ones at 60 mg/l concentration. The results showed that transformed plants have more tolerance to the herbicide than the non-transformed ones.
Keywords: Agrobacterium tumefaciens; dehalogenase E gene; dalapon; transgenics; SELECTABLE MARKER; GENE; CLONING; DNA; TUMEFACIENS; SEQUENCE; VECTOR